Innovative Approaches to Teaching Russian Language and Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The method of teaching the Russian language begins with teaching the language to elementary school students. The first method of teaching Russian is a practical technique. Psychological and pedagogical patterns of the educational process are similar to the needs of society. At the heart of these needs are the means of communication. Communication tools determine the ways of teaching Russian to students in accordance with their language characteristics. The method of teaching the Russian language consists of literary parts, language skills of students, grammar concepts, changes in the language system over time (assimilation) and other parts of language science. Methodology, Pedagogy, psychology and philosophy at the intersection of disciplines. These disciplines have a common interest.